ENHANCING HEALTH AWARENESS THROUGH COMMUNITY PARTICIPATION - Saribanon, Nonon; Gustiani, Widya; Aditya Kusuma, Sony; Apriani, Hesty; Aria, Angga (Universitas Nasional, 2021)
This Integrated Health System Innovation in Rahayu Village is an integrated and sustainable health program involving several stakeholders and related agencies. This program deals with health by integrating clean water programs as a health solution, agricultural programs for food self-sufficiency and nutrition improvement, and goat farming programs to support medicinal plant farming programs and organic vegetables. The study of the impact program using a qualitative approach, through FGDs and in-depth interviews, also observation and desk study on secondary data. This program has succeeded in raising awareness of healthy living and independence in solutions to the problems of the clean water crisis, health problems for children & families, and independence in fulfilling children's and family's nutrition.